Effects of dietary thyme (Zataria multiflora) extract on antioxidant and immunological responses and immune-related gene expression of rainbow trout (Oncorhynchus mykiss) juveniles - Ali Taheri Mirghaed (2020)
© 2020 Elsevier Ltd Effects of dietary hydroalcoholic extract of Zataria multiflora (ZE) on growth performance, plasma and hepatic antioxidant capacities, and humoral and skin mucus immune parameters were evaluated in rainbow trout (Oncorhynchus mykiss) juveniles. in vitro tests showed that ZE had antioxidant property comparable to butylated hydroxytoluene (BHT) at 100–200 μg/mL concentrations, although its antioxidant property was lower than BHT at concentration below 100 μg/mL. Moreover, ZE had anti-bacterial activity against Aeromonas hydrophila, which was 30–50% lower than that of tetracycline. After feeding the fish with diets supplemented with 0 (CT, 1 (ZE1), 2 (ZE2), and 3 (ZE3) g/kg ZE for eight weeks, there were no significant differences in growth performance and feed efficiency among the treatments; however, the fish in ZE2 and ZE3 treatments showed significantly higher survival than the fish in CT treatment. Blood leukocyte counts, plasma globulin, total immunoglobulin, lysozyme and bactericidal activity against A. hydrophila in ZE2 and ZE3 groups were significantly higher than that of CT group. All the ZE-treated groups had higher plasma complement activity compared to the CT group. Mucosal lysozyme and bactericidal activities of the ZE2 fish were significantly higher than the other treatments. Expression of tumor necrosis factor alpha, interleukin-1 beta, interleukin-6, and lysozyme genes increased in head kidney of the fish treated with ZE; the highest increases were related to the ZE2 treatment. Plasma total antioxidant (TA) activities of ZE2 and ZE3 treatments were significantly higher than that of the CT treatment. Plasma and hepatic superoxide dismutase (SOD) and catalase (CAT) activities of ZE2 group were significantly higher than the other treatments. Plasma malondialdehyde (MDA) levels were significantly lower in ZE2 treatment, compared to the other treatments. However, hepatic MDA level of ZE2 treatment was significantly lower than those of the ZE1 and CT treatments. In conclusion, dietary ZE supplementation level of 2 g/kg is suggested for rainbow trout feed supplementation to augment fish survival, antioxidant and immune strength.